Investigation of MHD and applied electric field effects in a conduit cramed with nanofluids - Umavathi, J. C.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
The numerical simulation is presented to discuss the impact of magnetic and electric fields on nanofluid in a conduit. The nanofluid obey Tiwari and Das one phase model. Copper, diamond, silicon-oxide, and titanium-oxide are used as nanoparticles keeping base fluid to be water. The vertical plates of the enclosure are maintained at unvarying temperatures such that right wall temperature is higher than the left wall temperature. The upper and lower walls are thermally insulated. The dimensionless balance equations are resolved adopting Southwell-Over-Relaxation method. The influence of pertinent parameters are displayed in graphs and analyzed in terms momentum and energy. The computations are operated for distinct characteristics. The results indicate that highest velocity and energy appears using titanium oxide and copper respectively. Magnetic filed lowers the momentum and amplify temperature. Heat transfer rate is boosted with titanium oxide nanoparticle, Hartman, Brinkman, Grashof numbers, solid volume fraction and downturn by aspect ratio at the cold plate.
Keywords: Electric current; Rectangular duct; Nanofluids; Southwell-over-relaxation method